Mapping task switching in frontal cortex through neuropsychological group studies - Shallice, Tim; Stuss, Donald T.; Picton, Terence W.; Alexander, Michael P.; Gillingham, Susan (Frontiers in Neuroscience, 2008)
This paper considers evidence provided by large neuropsychological group studies and meta-analyses of functional imaging experiments on the location in frontal cortex of the subprocesses involved in the carrying out of task-switching paradigms. The function of the individual subprocesses is also considered in the light of analyses of the performance of normal subjects.